KARTU REMI JAWA (KAREWA): STRATEGI EFEKTIF MENINGKATKAN MINAT ANAK DALAM PEMBELAJARAN AKSARA JAWA DENGAN SISTEM QUEEN CARD GAME - Nurmalita, Azza; Hastuti, Trias Mira; Hardiyanti, Tri (Pelita - Jurnal Penelitian Mahasiswa UNY, 2015)
This study aims to determine the effectiveness of using Kartu Remi Jawa (karewa) in learning to read the Javanese alphabets through a Queen Card Game system. In this study an experimental method was employed. The data were collected through pre test and post test. A group design was used to compare the results of the pre test and post test. The class was also divided into an experimental class and a control class. The treatment to the experimental class was the use of Karewa media. The result of this study, the effectiveness of the use of Karewa in learning through playing, cannot be seen through the Independent T-Test because the control class has a very high value compared with the experimental value of the class. considering this, the researchers only use Paired T-Test to see the effectiveness of using karewa. The effectiveness obtained is 30%. Based on these results it is necessary to the determination of the experimental class and control classes with the same capacity (balanced), for example through tests given beforehand. Secondly, researchers should be able to hold a good control of both control and experimental classes. Kartu Remi Jawa can be used as a medium of learning to enhance students' interest in the Javanese alphabets. This will certainly have an impact on the preservation of local culture in Java island. Key words: Kartu Remi Jawa (Karewa), interest in learning, Javanese alphabets, queen card game